The Use of Autologous Leucocyte Labelling in Patients With Fever Of Unknown Origin - E. V. Migunova; G. A. Nefedova; V. P. Nikulina; S. S. Petrikov; L. T. Khamidova (Неотложная медицинская помощь)
RELEVANCE. Patients with a systemic reaction to inflammation are often observed after adequate surgical intervention and/or treatment of the underlying disease. Laboratory tests indicate the presence of a pronounced inflammatory process, and instrumental diagnostic methods (ultrasound, computed tomography, radiography) do not always help in detecting the source of inflammation.THE AIM OF THE STUDY. Is to present the possibilities of radionuclide imaging (RI) using labelled autologous leucocytes to identify the source of infection.MATERIAL AND METHODS. 95 patients with fever of unknown origin were examined by the radionuclide diagnostic method. The data of computed tomography (CT), ultrasound, radiography (RG), laboratory tests (CRP, PCT, IL-6), the results of morphological examination in comparison with the results of RI were analyzed. Clinical examples are presented.RESULTS. With the help of RI, foci of inflammation were identified. Based on the data obtained, the treatment was adjusted, which contributed to the recovery of 80 patients. In 15 patients, because of generalized infection, a systemic inflammatory reaction and sepsis developed, leading to a fatal outcome.CONCLUSION. Radionuclide imaging (RI) using labelled autologous leucocytes in patients with fever of unknown origin allows us to obtain reliable visualization of areas of pathological infiltration and physiological distribution of cells. Based on the data obtained, it is possible to adjust the therapy, which helps increase treatment effectiveness.